Liberating Learning : Technology, Politics, and the Future of American Education - Moe, Terry M. and Chubb, John E. (San Francisco Jossey-Bass, 2009)
Technology can revolutionize schools ??? if we let it Imagine a cyber-school in an old steel mill where students from distant cities log in to learn. Or a Midwest charter school with state-of-the-art learning labs, where kids use laptops to manage their work
Include Notes and Index
Keywords: Public schools -- Technology and state -- Education--Effect of technological innovations on